The Evolution of the Trust System in the Mutual Fund Business in Indonesia (A Study Based on Islamic Law Perspective) - Dewi, Gemala (UI Scholars Hub, 2011)
The progressive development of International law can be seen also in the concept of trust in business transaction based on its evolution from time to time. This is because the trust institution, which is considered as an achievement of the Anglo-Saxon legal system that has tremendous benefit, actually started from the concept of separation between ownership and mastery in the form of charitable trust of waqf , known in Islamic law. Research proves that in the history of “Trust”, waqf is forerunner of the establishment of “Trust”. How the concept of waqf develops a business type of Mutual Fund that is in compliance with Sharia Law, is the problem that is discussed in this paper. By using a normative and comparative law method, this paper found that by implementing only Nazhir functions that reflect the concept of trust by means of Islamic Trust Fund (ITF), the benefit of the object of cash waqf can be multiplied. For this purpose, the Islamic Trust Fund concept is defined in the real meaning of cash waqf mandate which today can be used in business activities, other than worship sector0. With ITF concept like this does not preclude the general public to participate in purchasing units in the form of a business Sharia Mutual Funds (SMF), so thus also can create investment opportunities that also drives the wheels of development.